2013
DOI: 10.1259/bjr.20130173
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid damage-associated biomarkers of ionising radiation: current status and future relevance for radiology and radiotherapy

Abstract: Diagnostic and therapeutic radiation technology has developed dramatically in recent years, and its use has increased significantly, bringing clinical benefit. The use of diagnostic radiology has become widespread in modern society, particularly in paediatrics where the clinical benefit needs to be balanced with the risk of leukaemia and brain cancer increasing after exposure to low doses of radiation. With improving long-term survival rates of radiotherapy patients and the ever-increasing use of diagnostic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…In general, DSBs evoke a DNA damage response during which the DSB signal is amplified and several repair routes are induced involving proteins that can serve as biomarkers (4).…”
mentioning
confidence: 99%
“…In general, DSBs evoke a DNA damage response during which the DSB signal is amplified and several repair routes are induced involving proteins that can serve as biomarkers (4).…”
mentioning
confidence: 99%
“…Therefore, a common side effect observed in cancer patients undergoing chemotherapy or radiotherapy is bone marrow depletion. [30] A potential additional application of our liposomes is to deliver drugs that can protect bone marrow from destruction or help aid in the recovery of bone marrow at much higher concentrations than what can be achieved by systemic delivery of naked drugs. [31] The bone marrow liposome's long stability (Figure S5) and near 100% labeling efficiency (Figure S2) enable us to develop a kit ready for immediate use with adjustment of pH, labeling of PET radiotracer, and neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our findings with a previously used gene in GE biodosimetry, FDXR (Boldt et al 2012;Kabacik et al 2011;Knops et al 2012;Manning and Rothkamm;Paul and Amundson, 2008), which is regulated by p53 family and with our previous in vitro study (Khodamoradi et al In Press). In our pervious study, we found the dose response curve of the FDXR and RAD51 genes in response to different doses and 6 and 18 MV beam energies in human PBLs.…”
Section: Discussionmentioning
confidence: 99%